Pengaruh Bai Sawit Terhadap Tingkat Kesejahteraan Petani Kecamatan Kuta Makmur Kabupaten Aceh Utara - Murtala Murtala; AyiHerfendi AyiHerfendi; Syarifah Syafira (Jurnal Ekonomi Pertanian Unimal, 2023)
This study was conducted in Indonesia and aimed to examine the effect of rubber production, the dollar exchange rate, and inflation on rubber exports. The data analysis method used was multiple linear regression. The results showed that rubber production and inflation positively and significantly influenced rubber exports, while the dollar exchange rate negatively and significantly influenced rubber exports. Simultaneously, rubber production, the dollar exchange rate, and inflation positively and significantly influenced rubber exports in Indonesia, and the magnitude (R^2) of the effect of the amount of production, dollar exchange rate, and inflation on rubber exports was 0.5979 (59.79%)